2014
DOI: 10.1021/bi401356y
|View full text |Cite
|
Sign up to set email alerts
|

SB-RA-2001 Inhibits Bacterial Proliferation by Targeting FtsZ Assembly

Abstract: FtsZ has been recognized as a promising antimicrobial drug target because of its vital role in bacterial cell division. In this work, we found that a taxane SB-RA-2001 inhibited the proliferation of Bacillus subtilis 168 and Mycobacterium smegmatis cells with minimal inhibitory concentrations of 38 and 60 μM, respectively. Cell lengths of these microorganisms increased remarkably in the presence of SB-RA-2001, indicating that it inhibits bacterial cytokinesis. SB-RA-2001 perturbed the formation of the FtsZ rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 59 publications
1
47
0
Order By: Relevance
“…A taxane derivative, SB-RA-2001, was recently identified to have minimum host cytotoxicity and MIC 99 value (Huang et al 2006). The compound promotes the assembly of purified FtsZ and stabilizes FtsZ filaments and unlike paclitaxel, SB-RA-2001 did not promote and stabilize the assembly of tubulin (Singh et al 2014). Without affecting karyokinesis, SB-RA-2001 seems to inhibit the localization of FtsZ to form the Z-ring (Fig.…”
Section: :9mentioning
confidence: 92%
See 2 more Smart Citations
“…A taxane derivative, SB-RA-2001, was recently identified to have minimum host cytotoxicity and MIC 99 value (Huang et al 2006). The compound promotes the assembly of purified FtsZ and stabilizes FtsZ filaments and unlike paclitaxel, SB-RA-2001 did not promote and stabilize the assembly of tubulin (Singh et al 2014). Without affecting karyokinesis, SB-RA-2001 seems to inhibit the localization of FtsZ to form the Z-ring (Fig.…”
Section: :9mentioning
confidence: 92%
“…It inhibited the proliferation of Bacillus subtilis and Mycobacterium smegmatis cells and induced filamentation in these cells. It is proposed that the mechanism of action of SB-RA-2001 on FtsZ is similar to that of paclitaxel on microtubules (Singh et al 2014).…”
Section: :9mentioning
confidence: 99%
See 1 more Smart Citation
“…The main scaffold of taxane polycyclic core was kept unchanged in this study. SB-RA-2001 (40 in Figure 7) shows differences from paclitaxel (41 in Figure 7) mainly in two parts: (i) the alcohol at C-10 without the acetyl group; (ii) an unsaturated ester replaces the α-hydroxy-β-amido ester at C-13 [114]. These structural modifications resulted in better inhibition of B. subtilis FtsZ activity and showed antibacterial activity against both B. subtilis and M. smegmatis.…”
Section: Taxane Derivativesmentioning
confidence: 99%
“…Examples of commonly employed assays are a cell-based assay for inhibitors of the discovery of cell division inhibitors [63], malachite green determination of phosphate release during the turnover of GTP to GDP for the inhibition of GTPase activity [64], monitoring FtsZ assembly using light scattering [65,66], examination of cell morphology by difference interference contrast microscopy to determine the effect of agents on bacterial cell filamentation [64,67], bacterial growth inhibition and in vivo efficacy in a murine septicaemia model [64], (Table 1). For example, GTPase assays in the presence and absence of the neutral detergent Triton X-100 have been proposed in order to distinguish between specific and nonspecific (aggregation-based) ligand effects [35,68], but other research has shown that this detergent inhibits the assembly of both B. subtilis and E. coli FtsZ, casting doubt on its use in this regard [69].…”
Section: Ftsz Inhibitorsmentioning
confidence: 99%